(untitled) (Homoeopathy for All, 2024)
Migraine is one of the most common neurological disorders. It is classified as a primary headache disorder characterized by recurrent headaches, typically unilateral which lasts for 4-72 hours, associated with of nausea, vomiting and photophobia. The word Migraine is a corrupted form of the word ‘hemicrania’, which meant one sided headaches. Therefore it is usually thought of as one sided headaches. This article provides an overview of the aetiology, diagnosis, and appropriate general & homoeopathic management of this disorder.